Prison Vocational Labour Under Mandela Rules and Nigerian Prison Laws: A Comparative Study - Danjuma, Ibrahim; Nordin, Rohaida; Muhamad, Mohd Munzil (International Journal of Asian Social Science, 2018)
Prison Vocational Labour (PVL) is an integral aspect of the correctional facilities that provide prisoners with the ability to learn better life skills. Nowadays, most of the prisons have a directorate that is entrusted with the responsibility of training prisoners through PVL. The purpose of PVL is to impart employable skills so that they may be employed after release. Within the international legal framework, the United Nations Standard Minimum Rules for the Treatment of Prisoners (Mandela Rules) provides a benchmark to all States for the treatment of prisoners as well as the nature and conduct of PVL. In the context of Nigeria, the domestic legal framework which consists of Prison Act, Prison Regulations and Prisons Standing Orders define the nature of PVL and how it should be carried out at the Nigerian Prisons. This study examines the compatibility between Nigerian legal framework and Mandela Rules on the nature and conduct of PVL.